Computational models of risks to infrastructure - Skanata, Dejan; Byrd, Daniel M. (NATO science for peace and security series. Information and communication security, 2007)
Deals with programs of infrastructure risk. This title focuses on following issues such as: the state-of-the-art and practice, gaps between the arts and practices, ways to bridge the gaps, and future research directions.